Varieties of Victorianism - Day, Gary. author. aut Link
XII, 270 p.
Keywords: The essays collected here all take issue with the claim that the Victorian period is the antithesis of our own. They show how characteristic postmodern anxieties and celebrations concerning truth, certainty and identity informed Victorian culture at all levels. Covering everything from attitudes to drink to the poetry of Browning, from the Great Exhibition to the Elephant Man, this volume shows not only how the Victorians coped with these challenges but also what lessons they have for us today.